2021
DOI: 10.1021/acs.chemmater.0c04951
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Stability of Mixed-Halide Vacancy-Ordered Quadruple Perovskites

Abstract: The structural and optical properties of the halide substitutions of Br − and I − into Cs 4 M II M III 2 Cl 12 (M II = Cd 2+ , Mn 2+ ; M III = Bi 3+ , Sb 3+ ) have been investigated. All compositions adopt the ⟨111⟩ layered vacancy-ordered quadruple perovskite structure with R3̅ m space group symmetry. Through incremental halide substitution reactions, we show that significant bromide incorporation is possible (>25% for Cd 2+ -containing structures). The larger halide ions (Br − or I − ) preferentially occupy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…We hypothesize that this trend can be traced back to differences in anion polarizability. The ∼90° M–X–M bond angles seen in the 2H structure allow for the electron cloud around the halide ion to be polarized toward the inorganic cations, whereas the linear M–X–M bonds of the cubic structure do not permit polarization (in a dipolar sense) because the point symmetry of the halide site (4/ mmm ) possesses an inversion center. This effect may also help to explain why the cubic structure is stabilized to higher values of t for quaternary double perovskites than it is for ternary perovskites. When the two octahedral cations become different, it lowers the site symmetry of the halide site to 4 mm , which does not have an inversion center.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that this trend can be traced back to differences in anion polarizability. The ∼90° M–X–M bond angles seen in the 2H structure allow for the electron cloud around the halide ion to be polarized toward the inorganic cations, whereas the linear M–X–M bonds of the cubic structure do not permit polarization (in a dipolar sense) because the point symmetry of the halide site (4/ mmm ) possesses an inversion center. This effect may also help to explain why the cubic structure is stabilized to higher values of t for quaternary double perovskites than it is for ternary perovskites. When the two octahedral cations become different, it lowers the site symmetry of the halide site to 4 mm , which does not have an inversion center.…”
Section: Discussionmentioning
confidence: 99%
“…The Mn 2+ ions are completely substituted by Cd 2+ to form Cs 4 CdBi 2 Cl 12 with the same crystal structure. 38 Then Yb 3+ ions are incorporated into the Cs 4 CdBi 2 Cl 12 crystal to study the NIR emission of Yb 3+ (Fig. S10, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…First, the Bi 3+ ions are excited to the 1 P 1 state, followed by a fast relaxation to the 3 P 0 level. After that, two possible energy transfer processes occur: one is that the excitation energy of Bi 3+ can directly transfer to the neighboring Yb 3+ , resulting in the NIR emission; the other one is that the excitation energy absorbed by Bi 3+ transfers to Mn 2+ through a resonant Dexter-type energy transfer process, 38 followed by the subsequent energy transfer of excited Mn 2+ ions to the 2 F 5/2 state of Yb 3+ , which also contributes to the NIR emission of Yb 3+ , though this is a minor process compared with the direct energy transfer of Bi 3+ to Yb 3+ . Although the detailed energy transfer mechanism between Mn 2+ and Yb 3+ needs further investigation, the PLQY data (Table S4, ESI†) show that the quantum-cutting effect should hardly be involved in this dopant energy transfer and relaxation processes due to the insufficient energy input from Mn 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…The mixed halogen effect of Cs 4 M(II)M(III) 2 X 12 on the optoelectronic properties has been investigated in previous experiments. 49 They found that the larger halide ions (Br − or I − ) preferentially occupy the anion sites adjacent to the cation-vacancy layer. Thus, here the mixed halogen was also considered in our work.…”
mentioning
confidence: 99%
“…Therefore, in the following sections, Cs 4 M­(IV)­M­(II) 2 X 12 with R -3 m and C 2/ m symmetry were selected to be discussed. The mixed halogen effect of Cs 4 M­(II)­M­(III) 2 X 12 on the optoelectronic properties has been investigated in previous experiments . They found that the larger halide ions (Br – or I – ) preferentially occupy the anion sites adjacent to the cation-vacancy layer.…”
mentioning
confidence: 99%